Pretreatment of waste activated sludge by rotational generator of hydraulic shock - Sabina Kolbl Repinc; Gašper Rak; Blaž Stres; Uroš Novak; Blaž Likozar; Anže Prašnikar; Marko Blagojevič; Benjamin Bizjan (Ultrasonics Sonochemistry)
This study investigates hydrodynamic performance of a novel sludge pretreatment device based on periodic shock wave generation by a hydraulic hammer mechanism. A falling circular jet of thickened waste activated sludge was repeatedly impacted by a rotating blade, resulting in occurrence of hydraulic shock waves within the liquid region adjacent to the impact. The rotational generator of hydraulic shock (RGHS) treating 10 L of waste activated sludge was operated for 30 liquid passes and at two different rotational speeds producing blade impact velocities of 44 m/s and 70 m/s, respectively. At 70 m/s impact velocity and 30 passes, the device was able to achieve 41.3 % disintegration degree (DD), specific energy consumption (SEC) of 10.4 kWh/kg sCOD released and 9.0 % improvement of produced methane volume over unprocessed sample. Corresponding values for 44 m/s impact regime were DD = 18.7 %, SEC = 8.03 kWh/kg sCOD released and 33.1 % improvement in methane production. In both pretreatment regimes, sludge shear-dependent viscosity was reduced by about 60 %, while physicochemical analysis, FTIR spectra revealed substantial structural changes in WAS, namely median particle size reduction, degradation of proteins and polysaccharides, and microbial cell wall damage, what was notable also on SEM images. Compared to other rotary devices, the novel RGHS can achieve relatively high degree of sludge disintegration while consuming significantly less energy for sludge solubilization, and for methane production enhancement.